(untitled) (Research, Society and Development, 2021)
This article aims to analyze evidence on educational actions aimed at preventing falls from patients in the hospital environment. It is an integrative review that included studies that carried out educational actions directed at patients, family members and the hospital assistance team with a viem to preventing falls. Search performed in the databases: virtual health library, PubMed and Scopus, published between 2005 and 2020. The corpus of analysis comprised 19 articles. Most of the evidence in the articles refers to educational actions directed at the patient, Family members and/or the assistance team with various strategies in order to prevent falls, however studies that used mixed approaches obtained more striking results. The analysis indicated that the insertion of the patient is fundamental when thinking about educational actions with a view to reducing falls in the hospital environment. For educational actions to be successful, patients also need a greater contribution of knowledge, able to identify risk factors in that environment and, from that, be able to suggest, together with Family members and teams, priority actions to reduce them.